PHILOSOPHICAL APPLICATION IN THE PROBLEM OF SCIENTIFIC RESEARCH - Miñano Lecaros, Juan Guillermo (2016)
Basically, the problem philosophy is to solve if wheth-er the origin of things come from a fact realized by a supernatural being -expressed as an “idealistic” origin- or the other, which states, that the origin of things, is evolution of the matter itself and is known like “materialistic” origin. This is obviously held by great thinkers like Aristotle, Aquinas, Kant and Democritus, Bacon and Locke among others respec-tively. In this sense, these two opposed philosophical currents (idealism and materialism), expose the ways of conceptualizing the origin of the “thing” or object, generating a very wide series of currents that support what was previously expressed. However, for a much more pragmatic conceptualization for the realization of our research, we consider only these two basic phil-osophical currents. This will allow us to analyze and apply the philosophical concept in the development of the research problem and, above all, to determine the variables that make up the problem in the devel-opment of research.